Technologies for electrical power conversion, efficiency, and distribution : methods and processes - Antchev, Mihail Hristov, 1955- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
This book combines research, contemporary achievements, and emerging trends within electrical energy conversion technologies and renewable energy sources. The scholarly findings compiled provide a background for discussion of the problems and opportunities of power efficiency and energy conversion in order to develop innovative ways to implement such cutting-edge technologies in the future--Provided by publisher.
Keywords: Electric power.; Energy conversion.; Electric power production.; Electricity.; elektronické knihy; electronic books